2013
DOI: 10.1159/000355832
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Risk Factors for Internet Gaming Disorder: A Comparison of Patients with Addictive Gaming, Pathological Gamblers and Healthy Controls regarding the Big Five Personality Traits

Abstract: Engaging in online games has become increasingly important as a part of leisure activity in adolescents and adults. While the majority of people use these games in a healthy way, epidemiological studies show that some develop excessive use and symptoms that are related to those of substance-related addictions. Despite increasing research concerning the epidemiology of internet gaming disorder (IGD), predisposing factors have been examined to a lesser extent. Knowing about specific risk factors would help clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(193 citation statements)
references
References 55 publications
9
175
2
7
Order By: Relevance
“…In this context, MMOs require the development of an online character (avatar) through which the player interacts with both the virtual world and other players (Elliot et al 2012). Research has consistently demonstrated excessive online use behaviors among MMO players and higher rates of IGD prevalence compared to players of other game genres (Caplan et al 2009;Müller et al 2014;Stavropoulos et al 2016). More specifically, MMO players have been found to play longer, and exhibit irritability when not able to play (Berle et al 2015), as well as lower self-regulation, increased impulsivity, and reduced agreeableness (Collins et al 2012).…”
Section: Massively Multiplayer Online Gamesmentioning
confidence: 99%
“…In this context, MMOs require the development of an online character (avatar) through which the player interacts with both the virtual world and other players (Elliot et al 2012). Research has consistently demonstrated excessive online use behaviors among MMO players and higher rates of IGD prevalence compared to players of other game genres (Caplan et al 2009;Müller et al 2014;Stavropoulos et al 2016). More specifically, MMO players have been found to play longer, and exhibit irritability when not able to play (Berle et al 2015), as well as lower self-regulation, increased impulsivity, and reduced agreeableness (Collins et al 2012).…”
Section: Massively Multiplayer Online Gamesmentioning
confidence: 99%
“…The personality characteristics associated with IGD include neuroticism, sensation seeking, trait anxiety, state anxiety, and aggression [25]. Comparisons with pathologic gamblers indicate that low conscientiousness and low extraversion are specific characteristics of IGD [26]. High levels of impulsivity also have been associated with IGD [27,28].…”
Section: Factors Associated With Internet Gaming Disorder (Igd)mentioning
confidence: 99%
“…Maybe one of the most thoroughly tested and studied correlations of the model is the association between neuroticism and psychopathology. The influence of this factor on mental health has been consistently reported and there is extensive research, specially on its correlation with depression and anxiety, [6][7][8][9][10][11][12][13][14] but also with schizophrenia and psychotic disorders, [15][16][17] substance abuse, 18,19 internet gaming disorder, 20 the frequency in engaging in different risk behaviors, 21 response to treatment 13,22 and even health 23 and psychopathology in general.…”
Section: 5mentioning
confidence: 99%